2021
DOI: 10.1002/ijgo.13910
|View full text |Cite
|
Sign up to set email alerts
|

Pēpē‐infant sleep practices and sudden unexpected death in infancy in Aotearoa New Zealand

Abstract: Objective To explore pēpē [infant] sleep practices and the key motivators among selected Māori and non‐Māori māmā [mothers] in Auckland, New Zealand, in relation to the risk of sudden unexpected death in infancy (SUDI). Methods Qualitative research underpinned by a kaupapa Māori cultural framework was undertaken. In‐depth face‐to‐face interviews occurred in the homes of māmā with young pēpē born in Counties Manukau, Auckland. Interview transcripts were analyzed using general purpose thematic analysis. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The articles in this special edition use positive approaches. This is done in order to empower women in healthcare, 12 to develop and trial culturally safe and community-based approaches, 2,6 to partner with communities, 3,5 to employ Indigenous methods and knowledge, 8,14 to privilege Indigenous voices, 4,9,10,11 to move towards risk assessment and management tailored to Indigenous populations and context, 15,16 and to explore women's experiences in new ways. 1,9,13 Much of the research responds to the silence/invisibility of First Nations and Indigenous women by challenging the norms of women's healthcare provision, such as persistent discrepancies in structural/social determinants of health, healthcare access and health outcomes, systemic racism, and trauma.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The articles in this special edition use positive approaches. This is done in order to empower women in healthcare, 12 to develop and trial culturally safe and community-based approaches, 2,6 to partner with communities, 3,5 to employ Indigenous methods and knowledge, 8,14 to privilege Indigenous voices, 4,9,10,11 to move towards risk assessment and management tailored to Indigenous populations and context, 15,16 and to explore women's experiences in new ways. 1,9,13 Much of the research responds to the silence/invisibility of First Nations and Indigenous women by challenging the norms of women's healthcare provision, such as persistent discrepancies in structural/social determinants of health, healthcare access and health outcomes, systemic racism, and trauma.…”
mentioning
confidence: 99%
“…Macfarlane et al 14 explored infant sleep practices among Māori and non-Māori mothers in Aotearoa New Zealand, specifically the risk of sudden unexpected death in infancy, and found that the need for adequate sleep motivates many mothers to share a bed with their infant. The authors encouraged service providers to "respond to the lived experiences and cultural realities, values, and beliefs of māmā (mothers)", 14 a call that applies to all facets of Indigenous and First Nations women's health and wellbeing and is at the heart of this Special Issue. Now, more than ever, is the time for us all to go on the hikoi (journey) to reject the silence and acceptance around Indigenous disparities in death and morbidity.…”
mentioning
confidence: 99%
See 2 more Smart Citations